1997
DOI: 10.1107/s0021889897002422
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Anomalous Small-Angle X-ray Scattering Investigation of Carbon-Supported Electrocatalysts

Abstract: Anomalous small‐angle X‐ray scattering (ASAXS) of synchrotron radiation with X‐ray energies near the Pt‐L3 X‐ray absorption edge was used to examine the size distribution of nanometer‐sized catalyst particles in porous electrodes for electrocatalytic applications. Carbon‐supported platinum electrocatalysts with 5–80 wt% Pt were studied in situ in an electrochemical cell with a 1 M sulfuric acid electrolyte. The anodic oxidation was found to shift the particle size distribution from a mean size of 1.7 nm in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 1 publication
1
71
0
Order By: Relevance
“…14,[18][19][20][21][22] A comprehensive discussion of the ASAXS method and its use in characterizing carbon-supported metal catalysts can be found in several publications and textbooks. [23][24][25][26][27][28][29] One advantage this technique has is its ability to obtain element specific PSDs. From changes in the Pt and Cu PSDs obtained through ASAXS, Yu et al were able to show the in-situ formation of a Pt enriched shell surrounding a PtCu core through electrochemical Cu dissolution of a carbon supported Pt 25 Cu 75 electrocatalyst and Tuaev et al showed the same type of evolution for a Pt 25 Ni 75 electrocatalyst.…”
mentioning
confidence: 99%
“…14,[18][19][20][21][22] A comprehensive discussion of the ASAXS method and its use in characterizing carbon-supported metal catalysts can be found in several publications and textbooks. [23][24][25][26][27][28][29] One advantage this technique has is its ability to obtain element specific PSDs. From changes in the Pt and Cu PSDs obtained through ASAXS, Yu et al were able to show the in-situ formation of a Pt enriched shell surrounding a PtCu core through electrochemical Cu dissolution of a carbon supported Pt 25 Cu 75 electrocatalyst and Tuaev et al showed the same type of evolution for a Pt 25 Ni 75 electrocatalyst.…”
mentioning
confidence: 99%
“…ASAXS can be applied to monitor the changes in average crystallite size (i.e., particle size in first approximation) and particle size distribution upon cycling, as shown by Gilbert et al [48] (Figure 6 c). Moreover, thanks to the high accuracy of ASAXS measurements, the size changes caused by the growth of an oxide layer [52] or the surface reconstruction caused by de-alloying can be probed. [53] The complementarity between electron microscopy, X-ray scattering and X-ray absorption spectroscopy methods as supporting tools to study the degradation of nanoparticles emerges clearly through these examples.…”
Section: Degradation Of Supported Nanoparticles: Post-mortem Investigmentioning
confidence: 99%
“…The spacer lengths were calculated using the MNDO method. [45] The construction of the network structures is based on the assumption of the presence of an Alorganic monolayer on the particle surface, while the corresponding bond lengths were taken from the literature and the Cambridge Structural Database: (1) Al-Pt: 0.232 nm; [46] (2) Al-C: 0.187 nm; (3) Al-O: 0.232 nm. The thus-constructed Pt nanoparticles (1.2 nm) with the cross-linked spacers BDM and HPDB are illustrated in Figures 10 and 11, respectively.…”
Section: Modeling Of the Pt-spacer Interactionmentioning
confidence: 99%